KEKERASAN TERHADAP TOKOH UTAMA PEREMPUAN DALAM NOVEL THE GIRL WITH THE LOUDING VOICE KARYA ABI DARE - Ike Nurhasanah (Yayasan Nusantara Hasana Berdikari, 2024)
This research aims to describe the depiction of violence against the main female character in the novel The Girl With The Louding Voice by Abi Dare. The method used in this research is a descriptive qualitative method and uses an objective approach. The data source is the novel The Girl With The Louding Voice by Abi Dare. The data collected in this research is in the form of words or quotations. Data collection techniques include reading, listening and note taking techniques. The listening process is carried out by reading carefully so that the data needed in the research is found and then the data is recorded. The result of this research are that there is violence against women which is classified into three forms, namely physical violence, verbal violence and sexual violence. The physical violence experienced by the main character includes being hit, slapped and kicked. The verbal violence experienced by the main character is being threatened, shouted and belittled. The sexual violence experienced by the main character is in the form of forced sexual intercourse.